Roles of Endothelial Motilin Receptor and Its Signal Transduction Pathway in Motilin-Induced Left Gastric Artery Relaxation in Dogs - Li, HongYu; Yang, LanLan; Jin, Ying; Jin, ChunXiang (Frontiers in Physiology, 2021)
Background: Motilin increases left gastric artery (LGA) blood flow in dogs via the endothelial motilin receptor (MLNR). This article investigates the signaling pathways of endothelial MLNR. Methods: Motilin-induced relaxation of LGA rings was assessed using wire myography. Nitric oxide (NO) and cyclic guanosine monophosphate (cGMP) levels were measured using an NO assay kit and cGMP enzyme-linked immunosorbent assay (ELISA) kit, respectively. Results: Motilin concentration-dependently (EC50 = 9.1 ± 1.2 × 10−8 M) relaxed LGA rings precontracted with U46619 (thromboxane A2 receptor agonist). GM-109 (MLNR antagonist) significantly inhibited motilin-induced LGA relaxation and the production of NO and cGMP. N-ethylmaleimide (NEM; G-protein antagonist), U73122 (phospholipase C [PLC] inhibitor), and 2-aminoethyl diphenylborinate (2-APB; inositol trisphosphate [IP3] blocker) partially or completely blocked vasorelaxation. In contrast, chelerythrine (protein kinase C [PKC] inhibitor) and H89 (protein kinase A [PKA] inhibitor) had no such effect. Low-calcium or calcium-free Krebs solutions also reduced vasorelaxation. N-nitro-L-arginine methyl ester (L-NAME; nitric oxide synthase [NOS] inhibitor) and ODQ (soluble guanylyl cyclase [sGC] inhibitor) completely abolished vasodilation and synthesis of NO and cGMP. Indomethacin (cyclooxygenase inhibitor), 18α-glycyrrhetinic acid (18α-GA; myoendothelial gap junction [MEGJ] inhibitor), and K+ channel inhibition through high K+ concentrations or tetraethylammonium (TEA-Cl; KCa channel blocker) partially decreased vasorelaxation, whereas glibenclamide (KATP channel blocker) had no such effect. Conclusion: The current study suggests that motilin-induced LGA relaxation is dependent on endothelial MLNR through the G protein-PLC-IP3 pathway and Ca2+ influx. The NOS-NO-sGC-cGMP pathway, prostacyclin, MEGJ, and K+ channels (especially KCa) are involved in endothelial-dependent relaxation of vascular smooth muscle cells.